Volume and Volatility in the FX-Market: Does it matter who you are? - Geir H. Bjønnes; Dagfinn Rime; Haakon O. Aa. Solheim (Center for Economic Studies and ifo Institute (CESifo), 2002)
The relationship between volume and volatility has received much attention in the the literature of financial markets. However, due to the lack of data, few results have been presented for the foreign exchange market. Further, most studies contain only aggregate series, and can not distinguish between the impact of different instruments or participants.We study the impact of volume on volatility in the the FX-market using a unique data set of daily trading in the Swedish krona (SEK) market. The data set covers 95 per cent of worldwide SEK-trading, and is disaggregated on a number of reporting banks' buying and selling in five different instruments on a daily basis over a period of nine years. We find that volume in general depict a positive correlation with volatility. However, the strength of the relationship depends on the instrument used and the identity of the reporting bank. In particular we find that it is the large Swedish banks that dominate the relationship. These banks are probably also the best informed banks. We interpret this is as evidence that heterogeneous expectations are important to understand the volume-volatility relationship.
Keywords: 330; volume volatility relation; microstructure; exchange rates.